Postoperative Morbidity Risks Following Ileocolic Resection for Crohn's Disease Treated With Anti-TNF Alpha Therapy: A Retrospective Study of 360 Patients. Issue 2 (18th January 2018) - Jouvin, Ingrid; Lefevre, Jérémie H; Creavin, Ben; Pitel, Sophie; Chafai, Najim; Tiret, Emmanuel; Beaugerie, Laurent; Parc, Yann; ,
Abstract: Background: Despite the effectiveness of anti-TNF alpha (ATA) treatment to induce and maintain remission in Crohn's disease, surgical intervention is frequently required. Results of previous studies on the impact of anti-TNF on postoperative course are discordant. The aim of this study was to evaluate the impact of ATA on postoperative morbidity following ileocolic resection for Crohn's disease. Methods: A retrospective review of Crohn's disease patients undergoing ileocolic resection was performed. Patients receiving medical treatment ≤8 weeks prior to surgery were included and followed up for postoperative morbidity. The Clavien-Dindo classification was used for grading complications. Risk factors for postoperative morbidity were assessed on multivariable analysis. Results: A total of 360 patients underwent ileocolic resection for Crohn's disease between 2002 and 2013; 15.3% of patients had ATA ≤8 weeks prior to surgery. Laparoscopic resections were performed in 110 cases (31%), of which 6% were converted to an open operation. Primary anastomosis without the formation of a diverting ileostomy was performed in 301 cases. Overall morbidity was 24.2%, with a mortality rate of 0.8%. ATA use prior to surgery was identified as an independent risk factor for overall morbidity (odds ratio [OR], 2.05; 95% confidence interval [CI], 1.08–3.82; P = 0.027) and septic complications (OR, 2.14; 95% CI, 1.03–4.29; P = 0.04). In subgroup analysis of patients with a primary anastomosis, ATA use had no significant impact on septic or overall morbidity. Conclusions: Preoperative ATA use is a risk factor for overall postoperative morbidity and septic complications. However, the formation of a primary anastomosis should not be influenced by preoperative ATA use.